Spontaneous gastrointestinal perforation in cats: a retrospective study of 13 cases. Issue 10 (October 2015) - Bernardin, Fanny; Martinez Rivera, Laura; Ragetly, Guillaume; Gomes, Eymeric; Hernandez, Juan
Objectives: The aim of this study was to describe the clinical characteristics and the frequency of malignant vs non-malignant causes for spontaneous gastrointestinal perforation in cats. Methods: The medical records of cats diagnosed as having gastrointestinal perforation between August 2010 and July 2013 were reviewed. Diagnosis was confirmed by exploratory surgery. Patients with incomplete records, perforation due to external trauma, leakage at previous enterotomy or anastomotic sites, or foreign bodies were excluded. Each record was examined for different information pertaining to signalment, medical history, clinical and clinicopathological data, imaging findings, abdominal fluid examination, surgical findings, histopathological examination, treatment received after surgery and outcome. Results: Thirteen cats were included. Five of these cats had concurrent illnesses, including viral upper respiratory tract disease, pancreatitis and chronic kidney disease. Two cats had previously received non-steroidal anti-inflammatory drugs and four had received corticosteroids. Clinical signs and clinicopathological abnormalities were not specific. Six of 13 patients were diagnosed during surgery with gastric perforations, four patients with duodenal perforations and three patients with jejunal perforations. Histopathological examination of the ulcerated wall was performed in 11/13 cats. Alimentary lymphoma was diagnosed in six cats. Non-neoplastic lesions (lymphocytic– plasmacytic inflammatory bowel disease, necrotic suppurative enteritis) were observed in the other five cats. The major limitation of the study was the small sample size. Conclusions and relevance: Lymphoma may be a frequent cause of spontaneous perforation in cats. Therefore, histological examination of ulceration is essential in all cases. The direct and sole implication of anti-inflammatory administration in a gastrointestinal perforation is not clearly established in this study.